Therapies Targeting Trained Immune Cells in Inflammatory and Autoimmune Diseases - Municio, Cristina; Criado, Gabriel (Frontiers in Immunology, 2021)
The concept of trained immunity has recently emerged as a mechanism contributing to several immune mediated inflammatory conditions. Trained immunity is defined by the immunological memory developed in innate immune cells after a primary non-specific stimulus that, in turn, promotes a heightened inflammatory response upon a secondary challenge. The most characteristic changes associated to this process involve the rewiring of cell metabolism and epigenetic reprogramming. Under physiological conditions, the role of trained immune cells ensures a prompt response. This action is limited by effective resolution of inflammation and tissue repair in order to restore homeostasis. However, unrestrained activation of innate immune cells contributes to the development of chronic inflammation and tissue destruction through the secretion of inflammatory cytokines, proteases and growth factors. Therefore, interventions aimed at reversing the changes induced by trained immunity provide potential therapeutic approaches to treat inflammatory and autoimmune diseases like rheumatoid arthritis (RA). We review cellular approaches that target metabolism and the epigenetic reprogramming of dendritic cells, macrophages, natural killer cells, and other trained cells in the context of autoimmune inflammatory diseases.